Preparation of Nanostructured Cu2SnS3 Photocatalysts by Solvothermal Method - Qingyun Chen; Di Ma (International Journal of Photoenergy)
Nanostructured Cu-Sn-S powder was prepared by a relatively low-cost, simple, and green solvothermal method. Flower-like Cu2SnS3 nanostructures were successfully synthesized in 50 vol% ethanol water solution at 200 °C for 7.5 h. The structure and photophysical properties of the as-obtained samples were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, and UV-Vis diffusion reflectance spectroscopy. Results showed that the cubic and tetragonal Cu2SnS3 was obtained by varying the ethanol contents. The band-gap energy of tetragonal Cu2SnS3 nanocrystals is near the optimum for photovoltaic solar conversion in a single band-gap device.